Control of Blue Mold of Pear Fruit caused by Penicillim expansum using Local Plant Extracts and their Derivatives - H.S.Ismael, Jalal; A.Mahmood, Hazha (Sulaimani Journal for Pure and Applied Sciences, 2014)
Due to the fractionation of Hypericum triquetrifolium extract, it was found that the isolated Hypericin gave the inhibition percentage of about 93.76% and the fungus growth diameter average of 0.59 cm. The volatile oil extracted from Vitus agnus-castus significant effect on the growth of the fungus about 71.20% inhibition percentage and the fungus growth diameter average about 2.39 cm. However, the extraction of Nigella sativa had a significant effect on the fungus growth about 82.03% and the fungus growth diameter average about 1.43 cm due to 0.5 μl ml-1. For detection of secondary compound products for H. triquetrifolium by HPLC technique, five compounds (peaks) were detected, the higher percentage of the secondary compound, Hypericin, was 225.073 μg ml-1, this is the active ingredient of this plant. An experiment was conducted on the actual possibility of the highest concentration of the extracts, which gave the highest percentage of inhibition of fungus Penicillium expansum by immersing the fruits of pear (cv. Harme naska ) alone and mix with each other and found that the mixing process has given impressive results, so mixtures of the last four gave the highest percentage inhibition (100%) and on this basis can be relied upon recommendation, we can say that the mixture (Hypericum + Nigella + Zingiber) gave a 100% . This treatment is better because it does not exist in the composition of a chemical on the other hand give a guarantee for those who work in organic cultivation.
Keywords: Disease Management; Blue Mold; Penicillium expansum; Plant extracts; HPLC